Development of novel carbon thin film electrodes for electrochemical analysis of trace heavy metals in aqueous solutions - Wang, Zhaomeng (2013)
Contamination and mismanagement of water resources have released toxic metals such as mercury (Hg), lead (Pb), cadmium (Cd) and copper (Cu), etc. into the environment. The presence of these toxic metals in aquatic ecosystems affects directly or indirectly biota and human being. Hence, fast detection and determination of trace toxic heavy metals in aqueous solutions are necessary to reduce fatal cases due to misconsumption of polluted water. Anodic stripping voltammetry (ASV) has been widely used for detection of heavy metals in solutions due to its remarkably low detection limit (ng/L), capability of simultaneous determination of multi-elements, low operating power and relatively low cost. The stripping step of ASV can be pulse, squarewave, linear or staircase. Square-wave anodic stripping voltammetry (SWASV) has been recognized as a powerful technique for detection of trace heavy metals in various aqueous solutions, because of its unique accumulation/preconcentration of analyte species contained in the solutions. In the past, glassy carbon electrode (GCE) has been widely used in electroanalytical applications because of its robust and smooth surface nature, as well as a large potential window. However, its electroanalytical performance frequently suffers from gradual loss of surface activity. In order to improve reproducibility, stability and sensitivity, a bismuth (Bi) thin film was coated on a GC substrate whose surface was modified with a porous thin layer of polyaniline (PANI) via multipulse potentiostatic electropolymerization to form a novel type of Bi/PANI/GCE in this study. The new electrodes were successfully used to simultaneously detect Cd2+ and Pb2+ ions with reference to SWASV signals. The experimental results depicted that the environmentally-friendly Bi/PANI/GCEs had the ability to rapidly monitor trace heavy metals even in the presence of surface-active species in the solutions. The electroanalytical performance of GCEs coated with PANI-multiwalled carbon nanotube (MWCNT) nanocomposite coatings (PANI-MWCNT/GCE) was investigated by detecting the Pb2+ ions in a 0.1 M acetate buffer solution using SWASV. It was found that the PANI-MWCNT/GCEs had a better performance than the bare GCEs. Different solvents were attempted for better dispersion of MWCNTs in the PANI matrices for more sensitive stripping signals. The surface morphology and structure of the PANI-MWCNT/GCEs were examined using field emission scanning electron microscopy (FE-SEM), high resolution transmission electron microscopy (HR-TEM) and Raman spectroscopy, showing that the conductive PANI matrices worked as both a conductor to electrically connect the individual MWCNTs, and a binder to mechanically join the MWCNTs. Recently, graphene-based electrochemical sensors have also been developed to trace toxic heavy metals in aqueous solutions. Graphene possesses various unique properties with its atomic carbon layers of nanometer thicknesses, high electrical conductivity, fast transfer of electrons and alleviation of the fouling effect of surfactants. Graphene-based electrochemical sensors can be modified with nafion to improve their sensitivity in tracing heavy metals, thus greatly enhancing stripping current signals. There are several viable deposition techniques for fabrication of doped-graphene based electrode materials, such as chemical vapour deposition (CVD), physical vapour deposition (PVD) and spin coating, which are usually followed by high temperature treatment. In this work, few-layer graphene ultrathin films were synthesized via a novel solid-state carbon diffusion method by rapid thermal processing (RTP) of nickel/amorphous carbon (Ni/a-C) bilayers or Ni-C mixed layers, which were all sputtering-coated on silicon (Si) substrates with or without a silicon dioxide (SiO2) layer. For the Ni/a-C bilayer coated samples, the samples were heated at 1000 °C for 3 min to allow the C atoms from the a-C layers to diffuse into the top Ni layers to form C rich surface layers. Upon rapid cooling, the saturated C atoms in the C rich surfaces of the Ni layers precipitated and formed the ultrathin graphene films on the top of the remaining Ni/a-C layers. The formation of the ultrathin graphene films was confirmed by Raman spectroscopy, HR-TEM, electron diffraction, FE-SEM, X-ray photoelectron spectroscopy (XPS), and electrical impedance measurement by a 4-point probe. The formation mechanism of the graphene films was investigated with respect to Ni/a-C bilayer thickness and substrate surface condition (with or without a SiO2 layer). It was found that SiO2 nanowires arose on the thermally treated Ni/a-C bilayer coated Si substrates without a SiO2 layer, which may be due to the reactions between the thermally diffused Si atoms from the Si substrates and the residual oxygen in the RTP chamber, with the Ni layers as a catalyst. The key factors that prevent the formation of the SiO2 nanowires were discussed. The synthesized ultrathin graphene films were used as the working electrodes for simultaneous detection of trace Pb2+ and Cd2+ ions (as low as 7 nM) in acetate buffer solutions (pH 5.3) using SWASV. The effects of substrate surface condition, Ni layer thickness, and preconcentration potential and time on the structure and electrochemical properties of the graphene electrodes were systematically investigated. Compared to conventional diamond-like carbon (DLC) electrodes, the graphene electrodes developed in this study had better repeatability, higher sensitivity and higher resistance to passivation caused by surface active species in the solutions. The interference between the Cd2+ and Pb2+ stripping peaks was also investigated. With further modifications by using PANI porous layer and/or Bi nanoparticles, the graphene electrodes showed good repeatability, ultrahigh sensitivity (as low as 0.33 nM) and good resistance to passivation during the simultaneous detection of trace Pb2+ and Cd2+ ions. For the Ni-C mixed layer coated samples, the graphene thin films were synthesized using the same thermal processing method. During heating, the C atoms dissolved into the Ni lattices. However, during rapid cooling, the solubility of C atoms in Ni was sharply reduced, leading to the precipitation of excess C atoms and the formation of graphene thin films on the outer surfaces of the Ni-C layers. Raman spectroscopy and XPS were used to characterize the structure and composition of both the as-deposited and the thermally treated Ni-C coated samples with respect to the C content of the Ni-C thin films. The graphene thin film electrodes were used as the working electrodes in the simultaneous detection of trace Pb2+, Cd2+ and Cu2+ ions in acetate buffer solutions modified with bismuth (Bi). The Bi-modified graphene electrodes showed the significantly enhanced electroanalytical performance. The electroanalytical performance of the graphene electrodes was also investigated with respect to the Si substrate surface conditions (with or without a SiO2 layer).